Sucker rings from the humboldt squid Dosidicus gigas : the role of nanotubule architecture on the mechanical properties - Miserez, Ali (2014)
The suckers that line the arms and tentacles of squid are equipped with rigid toothed ringlike elements that increase the gripping power during prey capture and handling. The sucker rings of the Humboldt squid Dosidicus gigas, are fully proteinaceous and contain nanotubules with diameters ranging from 100 to 250 nm. It has been shown previously that the ensuing porosity is a prime determinant of the local elastic modulus [A. Miserez et al., Adv. Mater. 21, 401 (2009)]. Here additional nanoindentation data are presented together with structural analyses. The nanomechanical data support our model that the measured modulus is determined by the local porosity. The dry moduli reach ca. 8 GPa and are reduced about two-fold in the hydrated state. This surprisingly small reduction is discussed in relation to possible chemistries responsible for assembly of these structures.